2021
DOI: 10.3389/fbioe.2021.778496
|View full text |Cite
|
Sign up to set email alerts
|

Production of Recombinant Horseradish Peroxidase in an Engineered Cell-free Protein Synthesis System

Abstract: One of the main advantages of a cell-free synthesis system is that the synthetic machinery of cells can be modularized and re-assembled for desired purposes. In this study, we attempted to combine the translational activity of Escherichia coli extract with a heme synthesis pathway for the functional production of horseradish peroxidase (HRP). We first optimized the reaction conditions and the sequence of template DNA to enhance protein expression and folding. The reaction mixture was then supplemented with 5-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For the synthesis of other hemoproteins in E. coli lysate, where heme was supplemented as hemin, an optimal hemin concentration in the range of 0.15 µM ( Katayama et al, 2010 ) to 16.7 µM ( Zhu et al, 2015 ) was reported. As an alternative to heme supplementation, the heme can be generated in situ from glucose and glycine in the presence of 5-aminolevulinic acid synthase as shown for bacterial CYP ( Kwon et al, 2013 ) and HRP ( Park and Kim, 2021 ). However, because hemin is inexpensive and seems to have no major adverse effects towards the CFPS itself, there currently is no need for following that approach in the Sf 21-based CFPS system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis of other hemoproteins in E. coli lysate, where heme was supplemented as hemin, an optimal hemin concentration in the range of 0.15 µM ( Katayama et al, 2010 ) to 16.7 µM ( Zhu et al, 2015 ) was reported. As an alternative to heme supplementation, the heme can be generated in situ from glucose and glycine in the presence of 5-aminolevulinic acid synthase as shown for bacterial CYP ( Kwon et al, 2013 ) and HRP ( Park and Kim, 2021 ). However, because hemin is inexpensive and seems to have no major adverse effects towards the CFPS itself, there currently is no need for following that approach in the Sf 21-based CFPS system.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its open nature, reaction conditions can be directly manipulated, thus making it a versatile tool for protein production ( Gregorio et al, 2019 ). CFPS has proven valuable for the synthesis of numerous proteins ( Gregorio et al, 2019 ; Dondapati et al, 2020 ), including heme-containing proteins such as horseradish peroxidase (HRP) ( Zhu et al, 2015 ; Park and Kim, 2021 ) as well as bacterial cytochromes P450 ( Kwon et al, 2013 ), cytochrome C oxidase ( Katayama et al, 2010 ), and manganese peroxidase ( Ninomiya et al, 2014 ). These examples all used E. coli lysate, which is by far the most commonly used CFPS system.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of the DyP-type peroxidases as mentioned above, their heterologous expression in Escherichia coli (E. coli) and other expression systems remain challenging as is the case for other heme proteins (Ramzi et al, 2015;Ge et al, 2023). It hampers, for instance, the large-scale mechanistic investigation owing to the difficulties associated with the biosynthesis and availability of heme b, thereby limiting its native incorporation into the apo-proteins (Fiege et al, 2018;Park and Kim, 2021;Ge et al, 2023). It was previously shown that in vitro reconstitution is needed for obtaining functional DdDyP with the correct heme stoichiometry (Rai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of the DyP-type peroxidases as mentioned above, their heterologous expression in Escherichia coli ( E. coli ) and other expression systems remain challenging as is the case for other heme proteins ( Ramzi et al, 2015 ; Ge et al, 2023 ). It hampers, for instance, the large-scale mechanistic investigation owing to the difficulties associated with the biosynthesis and availability of heme b , thereby limiting its native incorporation into the apo-proteins ( Fiege et al, 2018 ; Park and Kim, 2021 ; Ge et al, 2023 ). It was previously shown that in vitro reconstitution is needed for obtaining functional Dd DyP with the correct heme stoichiometry ( Rai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%